Ukuran Perusahaan, Komite Audit, dan Kepemilikan Asing: Pengaruhnya Pada Pengungkapan Corporate Social Responsibility - Harahap, Daffa Fauzan; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 34 No 10 (2024), 2024)
This study aims to examine how the influence of company size, audit committee, and foreign ownership on CSR disclosure. This research was conducted on mining companies listed on the Indonesia Stock Exchange in 2018-2021. The method of determining the sample in this study used purposive sampling, so that a sample of 40 companies was obtained. Collecting data in this study using non-participant observation methods. This study uses multiple linear analysis techniques to determine the effect of company size, audit committee, and foreign ownership on CSR disclosure. The results of the analysis show that company size and audit committee have an effect on CSR disclosure, while foreign ownership has no effect on CSR disclosure. Research implies the importance for companies to provide information related to CSR disclosure for the sustainability of company operations.